Analisis Dan Implementasi Algoritma Rivest Code-5 Pada Keamanan Data - Sastya Hendri Wibowo; Diana Diana (Jurnal Penelitian Teknologi Informasi dan Sains, 2023)
The RC-5 algorithm is an algorithm with the encryption method using the symmetric method and processing in the form of a cipher block, the same keywords are used for the encryption and decryption processes. The testing and analysis phase consists of a). Testing the execution time of the key generation process (set up key) b). Testing the success of the encryption and decryption process on the client-server integration method c). Testing the success of the encryption and decryption process using the file operation method d). Comparison of overhead/file size before and after passing through the system. The testing phase and execution time analysis are carried out when using the file operation method where the test will be divided into 3 parts, namely the execution time for the key setup process, the encryption process, and the decryption process. Testing the success of the encryption and decryption process on the client-server integration method is divided into 2 parts, namely testing the encryption process and the decryption process. In testing the encryption process, the characters that will be sent to the server will be encrypted first with a key to becoming a ciphertext in the form of integer data. The test results obtained are 1). The execution time for key generation (set up key) is very fast, around 9-10 ns. 2). In the encryption and decryption process, the execution time depends on the size of the plaintext file. The larger the plaintext file size, the longer the execution time. Where for a file with a size of 1 kb requires an execution time of 50.6 ms in the encryption process. 3). There is no difference between the size of the file before entering encryption and after decryption. Where for files with a size of 500 bytes before entering the encryption process, a file of 500 bytes will be generated from the decryption process.